Zawartość metali ciężkich w glebach parków miejskich podlegających zróżnicowanym wpływom antropogenicznym = Content of heavy metals in urban park soils influenced by various anthropogenic changes - Baran, Stanisław; Bielińska, Elżbieta Jolanta; Kawecka-Radomska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this scientific paper was an examination of the heavy metal content in soils of selected parks situated in city centre zones as well as in the city suburbs. The content of heavy metals (Zn, Pb, Cu, Cd) in the examined soils showed high diversity depending on the intensity of anthropogenic pressure. The soils of parks situated in the city centre zone were characterised by a several-times higher concentration of the analysed trace elements than the soils of parks in the city suburbs.
Keywords: gleba; parki miejskie; metale ciężkie; zanieczyszczenie środowiska; soils; heavy metals; urban park; pollution